Performance evaluation of WirelessHART for factory automation - Petersen, S.; Carlsen, S. (2009 IEEE Conference on Emerging Technologies & Factory Automation, 2009)
The WirelessHART specification has given the industry access to their first open standard specifically aimed at wireless instrumentation for factory automation. For WirelessHART to be a viable solution for the process and automation industry, it has to provide a robust and reliable alternative to today's wired networks.This paper presents the results of a performance evaluation of a WirelessHART network deployed in an industrial environment. It also presents a performance analysis and deployment considerations for IEEE 802.11g coexistence. The conclusion of the paper is that a WirelessHART network is capable of reliable operation in an industrial environment, and when coexisting with three IEEE 802.11g networks.